The multidisciplinary and participatory process to develop the Rubric for Learning Communities about Health Approaches - ter Bogt, Maud J. J.; Tobi, Hilde; van Straten, Christine G. J. I.; Molleman, Gerard R. M.; van den Muijsenbergh, Maria E. T. C.; Bevelander, Kirsten E.; Fransen, Gerdine A. J. (Frontiers in Public Health, 2025)
IntroductionMany Dutch municipalities implement a systems approach to promote health behavior among citizens. Learning communities (LCs) in these approaches enable stakeholders to collaborate and learn from one another. To optimize LCs, insights are needed into how LCs create knowledge and put it into action. This study aimed to describe the multidisciplinary and participatory process to develop a rubric for multidisciplinary Learning communities about health approaches.MethodsThe rubric development took the form of a questionnaire, and was centred on a municipal healthy weight approach. The development consisted of three steps: (1) an iterative process involving literature and input from members and experts, (2) an expert session, and (3) qualitative and quantitative rubric reliability and usability tests.ResultsFive rubric versions were developed, resulting in a final version with eight constructs to assess LC partnership experiences, learning, and action. The rubric demonstrated a relatively high reliability. The rubric’s adequate usability performance was evidenced by its high response rate, which enabled researchers to gain insights into notable findings. These findings then facilitated discussions among LC members and formulated LC adjustments.DiscussionThe participative process played a crucial role in developing the rubric. LC facilitators are encouraged to apply the rubric. Future research is needed regarding the reliability and usability of the rubric in other settings.